People's rights - Alston, Philip (Oxford University Press, 2001)
The right to self-determination has been a driving force in international law and politics through much of the post-World War II period. In the 1970s it was joined by a number of other human rights attributed to peoples rather than to individuals, including rights to development, peace, a clean environment, and humanitarian assistance. In this volume the current and future significance of these so-called third-generation solidarity rights are examined by leading experts